OPERASI TIMBANG DI POSYANDU WILAYAH KERJA DAERAH PUSKESMAS SIKUMANA TAHUN 2023 - Oematan, Alsen Diamel; Yulianti, Maria Fransiska Priska; Syahputri, Nadia Eka; Adang, Gottfrieda Patiencia Taeng-Ob (Jurnal Media Tropika, 2024)
According to the Indonesian Nutrition Status Study (SSGI) report, East Nusa Tenggara is the province with the highest stunting rate nationally in 2021. Therefore, the government seeks to monitor growth and development as well as the provision of good and timely vitamin A to toddlers and children, and in the context of preventing and overcoming stunting, the government simultaneously implements the weighing operation program in all posyandu in each puskesmas, namely in February and August. Posyandu is required to monitor children's growth and development through the weighing operation program. Sikumana Health Center is one of the health centers in Kupang City that conducts a weighing operation program, which is carried out at each posyandu in the Sikumana Health Center working area. The weighing operation is an important momentum for community participation to improve the health of toddlers and children by monitoring children's growth and development, including overcoming malnutrition of toddlers which causes an increased risk of stunting, disruption of physical growth, mental development and intelligence of children. In this weighing operation activity, vitamin A and deworming drugs are also given and must be attended by all toddlers in the Sikumana UPTD Puskesmas work area. If toddlers are not present at the Posyandu, sweeping will be carried out, namely the act of measuring the height and weight of toddlers and children at the house concerned or picking up toddlers and children from home to the posyandu. In this case, students of the doctor education program, Faculty of Medicine and Veterinary Medicine Undana actively participated in Operation Weighing. This is in line with field practice activities in the IKKOM course. This field practice coincided with the weighing operation schedule at the posyandu in the Sikumana area, which was held for 5 days. This activity was attended by students from February 6 to February 10, with several activities such as anthropometric examination, administration of vitamin A, filling out the Non-Communicable Disease (NCD) questionnaire, introspective survey questionnaire, and checking blood sugar for the elderly, as well as distributing green bean porridge.